Fatores de risco associados ao abandono do tratamento de tuberculose no estado do Rio de Janeiro, Brasil, 2015-2019 (Brazilian Journal of Health Research, 2022)
Introduction: Abandonment of tuberculosis treatment is one of the main obstacles to control the disease in Brazil and in the world. In 2018, the state of Rio de Janeiro registered a 15.5% treatment abandonment rate in new cases, which is above the recommended by WHO. Objectives: Investigating factors associated with the abandonment of treatment according to sociodemographic and clinical-epidemiological characteristics of new tuberculosis cases in the state of Rio de Janeiro, Brazil. Methods: Data from the Health Notification Information System for the period 2015-2019 were used. The association of explanatory variables with treatment abandonment was explored through univariate and multivariate binary logistic regression models. Results: Out of the 14,831 individuals with tuberculosis included in the study, 1,852 abandoned treatment, representing 12.5% of the sample. Young males, with low schooling, of non-white color, smokers, and illicit drug users showed a predisposition to abandon treatment; the homeless population presented the highest chance of abandoning treatment. Conclusion: The study shows the importance of following these patient profiles to develop strategies that increase patient compliance to tuberculosis treatment.
Keywords: Tuberculose; Aderência ao Medicamento; Adesão do Paciente; Epidemiologia